The Role of Law in Supporting Secondary Uses of Electronic Health Information. (2015) - Ramanathan, Tara; Schmit, Cason; Menon, Akshara; Fox, Chanelle
Abstract : For decades, health information has been collected and shared for health care delivery and public health purposes. While the "primary use" of patient data for providing direct health care services is the cornerstone of health care practice, health departments rely on data sharing for research and analysis to support disease prevention and health promotion in the population. As the U.S. health system undergoes a digital revolution, health information that was previously captured in paper form now can be captured electronically. Electronic health information (EHI) has transformed the efficiency, capacity, and functions of the U.S. health system. For this reason, there is increased attention to the "secondary use" of electronic patient data for public health uses, including disease reporting and investigation, syndromic surveillance, and patient-specific or population-level communications about health conditions and their associated risk factors. Secondary uses may also encompass clinical research, licensure, and payment for services.